Historical Structural Racism in the Built Environment and Physical Health among Residents of Allegheny County, Pennsylvania. - Jones, Emily J.; Natale, Brianna N.; Blatt, Lorraine R.; Votruba-Drzal, Elizabeth; Miller, Portia; Marsland, Anna L.; Sadler, Richard C. (Journal of Urban Health, 2024)
Historical structural racism in the built environment contributes to health inequities, yet to date, research has almost exclusively focused on racist policy of redlining. We expand upon this conceptualization of historical structural racism by examining the potential associations of probable blockbusting, urban renewal, and proximity to displacement from freeway construction, along with redlining, to multiple contemporary health measures. Analyses linked historical structural racism, measured continuously at the census-tract level using archival data sources, to present-day residents' physical health measures drawn from publicly accessible records for Allegheny County, Pennsylvania. Outcome measures included average life expectancy and the percentage of residents reporting hypertension, stroke, coronary heart disease, smoking, insufficient sleep, sedentary behavior, and no health insurance coverage. Multiple regression analyses were conducted to examine separate and additive associations between structural racism and physical health measures. Redlining, probable blockbusting, and urban renewal were associated with shorter life expectancy and a higher prevalence of cardiovascular conditions, risky health behaviors, and residents lacking health insurance coverage. Probable blockbusting and urban renewal had the most consistent correlations with all 8 health measures, while freeway displacement was not reliably associated with health. Additive models explained a greater proportion of variance in health than any individual structural racism measure alone. Moreover, probable blockbusting and urban renewal accounted for relatively more variance in health compared to redlining, suggesting that research should consider these other measures in addition to redlining. These preliminary correlational findings underscore the importance of considering multiple aspects of historical structural racism in relation to current health inequities and serve as a starting point for additional research.